MENINGKATKAN HASIL BELAJAR PPKn MENGGUNAKAN MODEL PEMBELAJARAN SNOWBALL THROWING PADA SISWA SEKOLAH DASAR - kamarudin, kamarudin (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2022)
Abstract: The purpose of this study was to improve civics learning outcomes by using the snowball throwing learning model to third grade elementary school students at Negeri 6 Talaga Raya, Central Buton Regency. The design and model used in this research is the Kemmis and Taggart model which includes planning, implementation, observation, and reflection. This type of research is classroom action research (CAR). The results of the study were based on the results of observations, tests and pre-cycle evaluations of 33% or 5 students who completed from 15 students. Then the action of the first cycle achieved classical learning completeness of 53% or 8 students who completed from 15 students, and in the second cycle increased by 87% or 13 students who completed 15 students. Based on the results of the study, it can be concluded that the use of the snowball throwing learning model can improve learning outcomes in Civics lessons in grade III SD.